Power system operation enhancement modelling using MATLAB/Simulink - Somefunn Tobiloba Emmanuel; Ayodeji Olaoye Daniel; Longe Omowunmi Mary (E3S Web of Conferences)
This paper focuses on enhancing power system operations at the injection substation through the integration of renewable energy, modelled and simulated using MATLAB/Simulink. The study explores the incorporation of photovoltaic (PV) systems and energy storage solutions (ESS) to improve the substation’s operational efficiency and reliability. By simulating different scenarios, including PV integration and ESS operations, the results show a significant improvement in voltage stability, with an average voltage profile enhancement of 13.33% across all feeders. Additionally, the energy storage system scenario demonstrated the capability to continue supplying power to the feeders even after the 33 kV grid supply was cut off, further proving its effectiveness in ensuring grid stability during disruptions. These findings suggest that renewable energy integration, coupled with advanced control mechanisms, holds great potential for broader application in enhancing the reliability and sustainability of power systems.